Quaker Dreaming: The Lost Cotton Archive and the Aborigines of Van Diemen's Land - Brodie, Nick (Journal of religious history, 2016)
This article explores interactions between Tasmanian Aborigines and residents of a Quaker settler property in documented actuality and familial, regional, and scholarly memory. Debunking a recent suggestion that authentic Tasmanian Aboriginal religious rituals and mythologies were kept secret by these settlers for a century and a half, I argue that such mythologies, and stories of their transmission, are post-colonial inventions that attempt to render this part of the narrative of Quaker colonialism in Van Diemen's Land as principally humanitarian, with Quakers acting as a benignly aberrant exception to the wider phenomenon of settlers dispossessing Indigenous peoples. Demonstrating that these settlers colluded in wider colonial practices and policies, and were active participants in networks of scientific study of the Tasmanian Aborigines, this article serves as a case study of the multi-layered nature of colonial action and post-colonial historicism, and also points to a self-referential tendency in historiographies of colonial Tasmania. I suggest that the stories presented as an authentic body of Tasmanian mythology in Land of the Sleeping Gods (2013) unconvincingly attempts to reinscribe Quaker colonialism as pacifist and humanitarian, and I argue that in fact Quakers demonstrably contributed to the dispossessing of Tasmanian Aboriginal peoples from their traditional lands.